Strategi Peningkatan Kinerja Karyawan sebagai Upaya Peningkatan Kinerja Organisasi: Systematic Literature Review - Ranto, Dwi Wahyu Pril (Politeknik Piksi Ganesha Indonesia, 2024)
This study aims to review the strategies used by organizations to improve employee performance. This study uses a systematic literature review method. The data search method used was articles obtained through the Google Scholar database. Search for articles using keywords entered in the Publish or Perish application. The keywords used are employee improvement and performance strategies. The search for articles starts in 2018–2022. All articles searched are in Indonesian. Based on the search results obtained, 71 articles After the inclusion and exclusion processes, 20 potential articles were obtained for analysis. It can be concluded that the employee performance improvement strategy can be carried out by means of a SWOT analysis and testing of the variables that are the forming factors for the increase in employee performance. The research contribution is to provide an overview of the various methods that can be used by managers or company leaders in formulating employee performance improvement strategies.